Minat Olahraga Renang Bagi Lanjut Usia Di Kabupaten Boyolali Tahun 2021 - Optasari; Soenyoto, Tommy (Universitas Negeri Semarang, 2024)
It is hoped that swimming for the elderly can overcome various problems such as stress (in the mental sense) and is also able to stimulate the body to heal diseases (in the physical sense). Both as entertainment and as a means of swimming, swimming functions as health therapy (water therapy) to treat health problems such as hypokinemia (lack of exercise), musculoskeletal disorders, internal disorders and mental health disorders. Survey research is a method used to research and solve existing problems. The results of survey research are in the form of opinions or opinions from other people based on the object being observed. The data collection technique used by researchers is the interview method via questionnaire. The research results showed that 94% of respondents or 33 people were in the elderly category and 6% of respondents or 2 people were not in the elderly category. All respondents have an interest in sports and are interested in swimming in particular. Conclusion Based on the results of the research and discussion, it can be concluded that the elderly's interest in swimming in Boyolali Regency in 2021 is in the high category. The high interest of elderly people in swimming in Boyolali Regency is driven by the awareness factor of maintaining and maintaining health in old age, as well as the need for therapeutic processes for certain diseases.